Indomethacin serum concentrations in man. Effects of dosage, food, and antacid. Issue 4 (August 1976) - Emori, H W; Paulus, H; Bluestone, R; Champion, G D; Pearson, C
Abstract : In the use of anti-inflammatory compounds, sustained serum levels are thought to be related to drug efficacy. This study shows that frequent clinical administration of indomethacin can result in sustained serum levels of the drug and that food and antacid may have important modifying effects on serum indomethacin concentrations. After oral ingestion by fasting subjects, indomethacin rapidly appeared in the serum, usually reaching peak concentrations in 30 to 90 minutes. Food delayed and decreased the mean peak level; antacid delayed the peak and slightly enhanced subsequent concentrations. With multiple dose schedules plateau levels were reached after 24 hours. When a total daily dose of 150 mg was given as 25 mg every 4 hours peak concentrations were the same but fluctuations were smaller and average concentrations were higher than with a dosage of 50 mg every 8 hours.